Rapid Progressivity in a 62-Year-Old Circumcised Man with Penile Cancer: A Case Report - Patricia Prabawati; Farid Setyono (Indonesian Health Journal, 2024)
Penile cancer is a rare malignancy globally, including in Indonesia, with notable morbidity and mortality rates. This case report discusses a 62-year-old male with a penile mass, emphasizing the diagnostic challenges and the importance of early intervention in penile cancer cases. The patient presented with a progressively growing penile mass, dysuria, and penile pain. Clinical examination revealed a palpable, reddish mass on the penile shaft with unclear borders, a urethral fistula, and enlarged inguinal lymph nodes. Laboratory results showed white blood cell count, haemoglobin, platelet count, glucose, blood urea nitrogen, and creatinine abnormalities. An open biopsy suggested verrucous carcinoma, later revised to penile squamous cell carcinoma with inguinal lymph node metastases. Penile cancer, particularly squamous cell carcinoma, primarily affects older, uncircumcised men. Verrucous carcinoma, though rare, is associated with poor hygiene and lack of circumcision. Notably, misdiagnoses may occur due to the limited scope of open biopsies. Penile cancer is preventable, and its significant risk factors are modifiable. Penile carcinoma, although uncommon, poses severe consequences for affected individuals. Early diagnosis and intervention are crucial for improved outcomes. This case highlights the challenges in diagnosis, emphasizing the need for comprehensive assessments and awareness of the modifiable risk factors associated with penile cancer.